The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.5182/jaie.33.27
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Conversion of Paper Sludge Ash into Cation Exchanger Via Acid Leaching

Abstract: Alkali conversion of paper sludge ash into cation exchanger via acid leaching was examined. The extraction behaviors of major elements (Si, Al, Ca and Mg) from the ash into hydrochloric acid (1 mol/L HCl) and sulfuric acid (0.5 mol/L H 2 SO 4 ) aqueous solutions were almost same except Ca due to the formation of gypsum in the H 2 SO 4 solution. The ashes leached with 1 mol/L HCl and 0.5 mol/L H 2 SO 4 aqueous solutions were converted into zeolite-P and tobermorite, respectively, while the raw ash was converted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Previous studies have demonstrated that paper recycling ash [25,29,30,36,37,56] and post-consumer container glass [18][19][20][21] are suitable feedstocks for the hydrothermal synthesis of 11 Å tobermorite. PRA contains potentially reactive calcium (alumino)silicate phases (e.g., åkermanite, β-dicalcium silicate, anorthite, and gehlenite) that can be exploited in the hydrothermal synthesis of tobermorite, although its molar composition, 0.74 < [Ca]/[Si+Al] < 0.92 and 0.27 < [Al]/[Si+Al] < 0.44, also promotes the formation of katoite [29,36,37,56].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have demonstrated that paper recycling ash [25,29,30,36,37,56] and post-consumer container glass [18][19][20][21] are suitable feedstocks for the hydrothermal synthesis of 11 Å tobermorite. PRA contains potentially reactive calcium (alumino)silicate phases (e.g., åkermanite, β-dicalcium silicate, anorthite, and gehlenite) that can be exploited in the hydrothermal synthesis of tobermorite, although its molar composition, 0.74 < [Ca]/[Si+Al] < 0.92 and 0.27 < [Al]/[Si+Al] < 0.44, also promotes the formation of katoite [29,36,37,56].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that paper recycling ash [25,29,30,36,37,56] and post-consumer container glass [18][19][20][21] are suitable feedstocks for the hydrothermal synthesis of 11 Å tobermorite. PRA contains potentially reactive calcium (alumino)silicate phases (e.g., åkermanite, β-dicalcium silicate, anorthite, and gehlenite) that can be exploited in the hydrothermal synthesis of tobermorite, although its molar composition, 0.74 < [Ca]/[Si+Al] < 0.92 and 0.27 < [Al]/[Si+Al] < 0.44, also promotes the formation of katoite [29,36,37,56]. Accordingly, stoichiometric additions of silicate-bearing reagents such as sodium metasilicate or silica have been shown improve the tobermorite yield by appropriately tailoring the constituent ratios to 0.80 < [Ca]/[Si+Al] < 0.85 and 0.0 < [Al]/[Si+Al] < 0.18 [25,36,37].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations